Physical foundations of continuum mechanics - Murdoch, A. I. (Cambridge University Press, 2012)
Ian Murdoch's Physical Foundations of Continuum Mechanics will interest engineers, mathematicians and physicists who study macroscopic behavior (for example, solid mechanics or fluid dynamics) or engage in molecular dynamical simulations. Unlike other works on the subject, Murdoch's book examines physical assumptions implicit in continuum modelling from a molecular perspective. By doing so, this book clarifies physical interpretations of concepts and fields by emphasising their microscopic origin and sensitivity to scale. Murdoch expertly applies these concepts to theories of mixtures, generalized continua and fluid flow through porous media. This unique and thorough work is an authoritative reference for both students and experts in the field.